Propuesta de rehabilitación patrimonial de la “Casa Velez Merino” para uso de la carrera de arquitectura - Veloz Abarca, Sandra Abigail (2018)
The buildings of the historic center of Riobamba city have been, over time, an emblem of heritage and tradition. However, these values have been reduced due to abandonment and the high economic value that maintenance demands for their owners. For this reason, this project focuses on the recovery of the "Casa Vélez-Merino" through a design of heritage rehabilitation taking into account the state of abandonment and deterioration of this property. As part of the rehabilitation project of the heritage house, a new use of an educational nature is proposed for the development of academic activities of the Architecture Career of the National University of Chimborazo. The new use of the "Casa Vélez-Merino", as the headquarters of the Architecture career, aims to contribute to the urban environment and integrate elements and modern architectural typologies such as minimalism with contemporary materials such as steel, glass and concrete. The project is complemented with the projection of new areas such as workshop classrooms, bar-restaurant, multipurpose room, plotting and printing center, layout and topography laboratory and the teachers' room that the Architecture course requires. Additionally, a place of cultural character is proposed, in this open space various academic activities will be developed. For the elaboration of the project, the type of inductive research is applied, which allows to obtain information duly supported, constituting the basis for the fulfillment of the objectives